PENINGKATAN SARANA DAN PENGETAHUAN UNTUK MENDUKUNG PENERAPAN E-RAPOR DAN UKS DI MIM POTRONAYAN 1 - Supriyono, Heru; Isnen, Nur Muhammad Akbar; Murdiyanto, Dendy (Universitas Muhammadiyah Surakarta, 2019)
The partner of this Community Partnership Program (PKM) service are Potronayan Ibtidaiyah Muhammadiyah (MIM) 1. The main problems raised in this activity are two, namely schools have not been able to implement e-report cards or known as digital report cards (ARD) applications and the problem is not yet the optimal role of the school health business (UKS), especially the school dental health business (UKGS). The purpose of this activity is to improve the supporting facilities for implementing e-report cards and increase the knowledge of teachers and students to support UKS and UKGS. The method of implementing the activity is the application of computer infrastructure to support the application of e-report cards and the implementation of training and application of Android applications to increase knowledge about maintaining oral health and UKS. The results obtained from this activity are partners already have a computer infrastructure that is in accordance with the needs for the application of e-report cards and teachers and students have received training and Android applications to improve knowledge of dental and mouth maintenance. Evaluation results show that the Android application that is applied is able to make learning about oral health more enjoyable when compared to just using printed material.